2023
DOI: 10.3390/vaccines11020358
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibody Dynamics in Healthcare Workers after mRNA Vaccination

Abstract: Since the emergence of SARS-CoV-2, maintaining healthcare worker (HCW) health and safety has been fundamental to responding to the global pandemic. Vaccination with mRNA-base vaccines targeting SARS-CoV-2 spike protein has emerged as a key strategy in reducing HCW susceptibility to SARS-CoV-2, however, neutralizing antibody responses subside with time and may be influenced by many variables. We sought to understand the dynamics between vaccine products, prior clinical illness from SARS-CoV-2, and incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…In this current study, a recent Omicron BA.5 infection was not associated with statistically significant higher anti‐RBD concentrations, although the recently infected HCWs had 3‐fold higher anti‐RBD IgG median concentrations than infection‐naive HCWs. Nevertheless, all HCWs had detectable anti‐RBD IgG antibodies, which is in line with other studies showing waning but yet sustained anti‐RBD antibodies levels up to 9 months after mRNA vaccinations 17–19 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this current study, a recent Omicron BA.5 infection was not associated with statistically significant higher anti‐RBD concentrations, although the recently infected HCWs had 3‐fold higher anti‐RBD IgG median concentrations than infection‐naive HCWs. Nevertheless, all HCWs had detectable anti‐RBD IgG antibodies, which is in line with other studies showing waning but yet sustained anti‐RBD antibodies levels up to 9 months after mRNA vaccinations 17–19 …”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, all HCWs had detectable anti-RBD IgG antibodies, which is in line with other studies showing waning but yet sustained anti-RBD antibodies levels up to 9 months after mRNA vaccinations. [17][18][19] Protection against reinfection is considered to be reduced against the Omicron variant in comparison to previous SARS-CoV-2 variants. 20 The proportion of HCWs who were considered positive for the presence of Omicron BA.5 nABs was increased in both prior-infected groups, and inhibition activity was substantially higher in the recently…”
Section: Sars-cov-2-specific T-cell and Antibody Responses In Prior-i...mentioning
confidence: 99%
“…Nevertheless, all HCWs had detectable anti-RBD IgG antibodies, which is in line with other studies showing waning but yet sustained anti-RBD antibodies levels up to nine months after mRNA vaccinations. [17][18][19] Protection against reinfection is considered to be reduced against the Omicron variant in comparison to previous SARS-CoV-2 variants. 20 The proportion of HCWs who were considered positive for the presence of Omicron BA.5 nABs was increased in both prior-infected groups, and inhibition activity was substantially higher in the recently Omicron BA.5 infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the present study, we observed a relationship between vaccination-induced change in skin temperature and nAB that was a stronger predictor of the 6-month than the 1-month outcome. There are a few other reports examining the association between reactogenicity to SARS-CoV-2 vaccination and subsequent nAB, but interpretability is limited due to low samples sizes (4 to 8 per condition), 22 the analysis only of nAB trajectories over time, 23 which are confounded by absolute levels given that higher decay rates correlate with higher initial levels, 11 and the use of a mixed sample of mRNA and adenoviral vector vaccine recipients. 24 There are several key strengths of our study compared to the previous large studies.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the presence of at least one systemic symptom was associated with higher nAB at 12-19 days after dose two (10) and at 54 days after dose three (9). There are a few other reports examining the association between reactogenicity to SARS-CoV-2 vaccination and subsequent nAB, but interpretability is limited due to low samples sizes (4 to 8 per condition) (19), the analysis only of nAB trajectories over time (20), which are confounded by absolute initial levels (11), and the use of a mixed sample of mRNA and adenoviral vector vaccine recipients (21).…”
Section: Discussionmentioning
confidence: 99%